The Constitutional Right to Free Communication of the Institutionalized Resident - Gostin, Lawrence O. (1974)
This article comes from the notes and comments section of the North Carolina Central Law Journal from 1973. Justified by the generic first amendment protection to unabridged expression and association, a United States citizen cannot be unreasonably denied the right to communicate by mail; by telephone; with legal counsel; with the opposite sex; with others. In most states where such a citizen becomes mentally ill, the person may be involuntarily civilly committed. Although there is no justification for such a commitment beyond the fact that the individual is sick and is in need of care, often the individual's first amendment freedoms are restricted while a resident of a mental institution. This article will focus on the extent to which such restrictions violate the constitutional right of free expression and association, e.g. by mail, by telephone, with legal counsel, with the opposite sex, by general visitation